Conceptual Model for the Use of Smart Glasses in Ubiquitous Teaching (U-Teaching) - Atiq, A; Saha, S; Mirza, F (Association for Information Systems (AIS), 2019)
Smart glasses, a wearable headset technology, currently trending provides hands-free and augmented reality features. This paper looks at the research around mediated-reality tools to improve the delivery of education. Despite its potential, it has not seen widespread use in education. A suitable implementation framework and pedagogy have been proposed so that smart glasses can be used towards creating digitally-mediated learning (DML) environments. Aurasma is recommended as the implementation framework after a comparison with other frameworks based on factors such as cost, ease-of-use, and accessibility among others. For a suitable pedagogy, new assessment strategies, content personalization, and the use of 3-D learning spaces are recommended. It is argued, that the recommended framework and the pedagogy approach have the potential to improve learning environments for teachers and students. However, there are privacy concerns due to the pervasive nature of Augmented Reality (AR). In the current research, the overall learning environment is considered.